Actor, movement, space in Oskar Schlemmer‘s theatrical concept - Detcheva, Violeta (Young Scientific Music and Dance Forum : Conference with international participation, 2021)
The Theatre Concept of Bauhaus continued the main ideas of its founders. It found its shape in Oskar Schlemmer‘s ideas of triadic ballet, demonstrated in various theatrical experiments, which he directed as a leader of the theatre section of Bauhaus. His interest in the canons of movement led him to the concept of Design-in-Motion. The correlation, the color-sound movement of the actor in space is crucial to the comprehension of the overall impact on the senses of the spectator. It determines the concept of anti-mimetic theatre, which is inspired by dance and acrobatics. This theatre of the senses and ideas is based on the picture rather than the drama. It seeks for a holistic impact and metaphysical suggestions on the base of music, mechanics and mathematics. It renounces the drama, its linear narrative and the imitation. The analysis of the Bauhaus Theatre through the concepts of Oskar Schlemmer, shows their impact on contemporary dance, on Bob Wilson‘s theatre and performance.